Using Evidence-Based Practice: A Case Study. (Kairaranga, 2014)
This research reports on the application of aspects of a model of evidence-based practice (EBP) which were used to review a behaviour management programme. Special education practitioners employed at the Aotearoa/New Zealand Ministry of Education (MOE) drew from MOE principles and practices, as well as their professional expertise as they reviewed and critiqued the Collaborative Problem Solving Model (CPS). This study reveals two critical aspects when applying an evidence-based practice (EBP) process: understanding of research, and using a structured process. The article discusses a range of benefits and reports on the compatibility of the behaviour management programme with MOE principles and practices.